2009
DOI: 10.1111/j.1600-0870.2008.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Different approaches to model error formulation in 4D-Var: a study with high-resolution advection schemes

Abstract: A B S T R A C T All numerical models are imperfect. Weak constraint variational data assimilation (VDA), which provides a treatment of the modelling errors, is studied; building on the approach of Vidard et al. (Tellus, 56A, pp. 177-188, 2004). The evolution of model error (ME) is modelled using ordinary differential equations, which involve a scalar parameter. These approaches were tested using different high-resolution advection schemes. The first set of experiments were constructed to see if it is possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…As a result, given a fixed value for σ 2 o and either N or L, it is possible to choose a value for L and N respectively, that minimises the error in the analysis vector due to numerical model error and observation errors. The result for N in some way works towards answering the question posed by Akella et al [15] as to whether increasing the number of discretisation points would continue to decrease the effects of discretisation errors on the results of 4D-Var. In this instance, we have shown that when considering numerical model and observation errors in strong constraint 4D-Var, increasing the number of discretisation points past the optimal value of N when considering a full sets of observations, would result in an increase in the error in the analysis vector.…”
Section: Lemmamentioning
confidence: 94%
See 3 more Smart Citations
“…As a result, given a fixed value for σ 2 o and either N or L, it is possible to choose a value for L and N respectively, that minimises the error in the analysis vector due to numerical model error and observation errors. The result for N in some way works towards answering the question posed by Akella et al [15] as to whether increasing the number of discretisation points would continue to decrease the effects of discretisation errors on the results of 4D-Var. In this instance, we have shown that when considering numerical model and observation errors in strong constraint 4D-Var, increasing the number of discretisation points past the optimal value of N when considering a full sets of observations, would result in an increase in the error in the analysis vector.…”
Section: Lemmamentioning
confidence: 94%
“…Examining expression (15), we see that the aliasing error inM has a shifted b-periodic nature. Raising the matrixM to the power l −[l] b results inM being raised to a power which is an integer multiple…”
Section: Definition 2 (The Mnimc Scheme)mentioning
confidence: 96%
See 2 more Smart Citations
“…An alternative approach constructs autoregressive models of background errors based on the short-term linearized model dynamics (Constantinescu et al, 2007a). Multivariate, multidimensional background error covariance matrices that maintain the geostrophic and hydrostatic balance have been proposed in Akella and Navon (2009).…”
Section: Introductionmentioning
confidence: 99%